Restoring movement representation and alleviating phantom limb pain through short‐term neurorehabilitation with a virtual reality system. (5th July 2016) - Osumi, M.; Ichinose, A.; Sumitani, M.; Wake, N.; Sano, Y.; Yozu, A.; Kumagaya, S.; Kuniyoshi, Y.; Morioka, S.
Abstract: Background and Objective: We developed a quantitative method to measure movement representations of a phantom upper limb using a bimanual circle‐line coordination task (BCT). We investigated whether short‐term neurorehabilitation with a virtual reality (VR) system would restore voluntary movement representations and alleviate phantom limb pain (PLP). Methods: Eight PLP patients were enrolled. In the BCT, they repeatedly drew vertical lines using the intact hand and intended to draw circles using the phantom limb. Drawing circles mentally using the phantom limb led to the emergence of an oval transfiguration of the vertical lines ('bimanual‐coupling' effect). We quantitatively measured the degree of this bimanual‐coupling effect as movement representations of the phantom limb before and immediately after short‐term VR neurorehabilitation. This was achieved using an 11‐point numerical rating scale (NRS) for PLP intensity and the Short‐Form McGill Pain Questionnaire (SF‐MPQ). During VR neurorehabilitation, patients wore a head‐mounted display that showed a mirror‐reversed computer graphic image of an intact arm (the virtual phantom limb). By intending to move both limbs simultaneously and similarly, the patients perceived voluntary execution of movement in their phantom limb. Results: Short‐term VR neurorehabilitation promptly restored voluntary movement representations in the BCT and alleviated PLP (NRS: p  = 0.015; 39.1 ± 28.4% relief, SF‐MPQ: p  = 0.015; 61.5 ± 48.5% relief). Restoration of phantom limb movement representations and reduced PLP intensity were linearly correlated ( p  < 0.05). Conclusions: VR rehabilitation may encourage patient's motivation and multimodal sensorimotor re‐integration of a phantom limb and subsequently have a potent analgesic effect. Significance: There was no objective evidence that restoring movement representation by neurorehabilitation with virtual reality alleviated phantom limb pain. This study revealed quantitatively that restoring movement representation with virtual reality rehabilitation using a bimanual coordination task correlated with alleviation of phantom limb pain.